BIOSORPTION OF CADMIUM (Cd) AT GREEN COCO FIBER (Cocos nucifera) WAS ACTIVATED BY USING ATOMIC ABSORPTION SPECTROPHOTOMETER (AAS) METHOD - Syamsidar HS; Yuniati Udin (PROSIDING SEMINAR KIMIA, 2015)
Various human activities are potentially produce heavy metal waste. The waste if it is not treated properly will cause environmental pollution and are toxic to organisms living including humans. Biosorbent has several advantages, including relatively low cost and easy to obtain.The use coco fiber as biosorbent is one good use of waste to reduce environmental pollution. Has conducted research cadmium biosorption (Cd) on biosorbent green coconut coir fiber (Cocos Nucifera) activated NaOH. This study includes the determination of the optimum concentration for activation biosorbent base, determination of optimum pH, determining the optimum time and capacity biosorption by using atomic absorption spectrophotometer (AAS).The results showed that the highest concentrations of NaOH activation biosorbent is 1.8 M or 11.2310 mg / L. The highest pH used by biosorbent activated is pH 2 or 19.6 mg / L, the highest timing needed to adsorb Cd is 30 minutes ie 14.7941 mg / L, whereas the highest biosorption capacity at a concentration of 70 ppm is 32.2882 mg / L